Gait generation for a simulated hexapod robot : a nonlinear dynamical systems approach - Campos, R. (2010)
The capacity of walking in a wide variety of terrains is one of the most important features of hexapod insects. In this paper we describe a bio-inspired controller able to generate locomotion and reproduce the different type of gaits for an hexapod robot. Motor patterns are generated by coupled Central Pattern Generators, formulated as nonlinear oscillators. In order to demonstrate the robustness of the controller we developed a simulation model of the real Chiara hexapod robot where are described the most important steps of its development. Results were performed in simulation using the developed model of the Chiara hexapod robot.